2022
DOI: 10.3390/microorganisms10122382
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila and Faecalibacterium prausnitzii in Immune-Related Diseases

Abstract: Probiotics and synbiotics are used to treat chronic illnesses due to their roles in immune system modulation and anti-inflammatory response. They have been shown to reduce inflammation in a number of immune-related disorders, including systemic lupus erythematosus (SLE), human immunodeficiency virus (HIV), and chronic inflammatory skin conditions such as psoriasis and atopic dermatitis (AD). Akkermansia muciniphila (A. muciniphila) and Faecalibacterium prausnitzii (F. prausnitzii) are two different types of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 105 publications
0
50
0
Order By: Relevance
“…Faecalibacterium is a genus associated with a healthy status, since their species are butyrate producers, taking special relevance to F. prausnitzii. Previous studies evaluating intestinal microbiota in OB and NW individuals have reported a decrease in this bacteria in the first one [62], which is one of the most reported lean-associated genera [63] Anaerostipes, a genus belonging to the family Lachnospiraceae of the phylum Firmicutes, was also found in significantly higher abundance in NW individuals. Previous studies have shown that this genus was significantly overrepresented in subjects with low inflammatory index [64] and increased in healthy controls when different pathologies have been evaluated as, for example, major depressive disorder [65].…”
Section: Analysis Of the Gut Microbiota Compositionmentioning
confidence: 75%
“…Faecalibacterium is a genus associated with a healthy status, since their species are butyrate producers, taking special relevance to F. prausnitzii. Previous studies evaluating intestinal microbiota in OB and NW individuals have reported a decrease in this bacteria in the first one [62], which is one of the most reported lean-associated genera [63] Anaerostipes, a genus belonging to the family Lachnospiraceae of the phylum Firmicutes, was also found in significantly higher abundance in NW individuals. Previous studies have shown that this genus was significantly overrepresented in subjects with low inflammatory index [64] and increased in healthy controls when different pathologies have been evaluated as, for example, major depressive disorder [65].…”
Section: Analysis Of the Gut Microbiota Compositionmentioning
confidence: 75%
“…With this in mind, the lower abundance of Firmicutes , which means lower butyrate production, is not an unexpected finding in the AE group. Among Firmicutes , the butyrate-producing Faecalibacterium prausnitzii had been widely proved to be associated with a good response to immune checkpoint inhibitors (ICIs) and a higher risk of developing irAEs (in particular, immune-related colitis) in metastatic melanoma patients [ 17 ]. On the other hand, among Bacteroidetes , Akkermansia muciniphila seemingly plays a protective role in the occurrence of colitis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The species Akkermansia muciniphila of the phylum Verrucomicrobia may be associated with pain inhibition [ 34 ]. A. muciniphila also plays a role in controlling immunological function, enhances the synthesis of antimicrobial peptides and improves gut homeostasis [ 35 ]. Many of the intestinal microbes produce neurotransmitters, including acetylcholine produced by Lactobacillus plantarum , dopamine produced by Proteus vulgaris , Bacillus , and Serratia marcescens , GABA produced by Lactobacillus and Bifidobacterium , histamine produced by Citrobacter and Enterobacter , norepinephrine produced by Saccharomyces , Bacillus , and E. coli and serotonin (5-HT) by E. coli , Enterococcus , Candida and Streptococcus [ 36 ].…”
Section: Dysbiosis—imbalance In the Gutmentioning
confidence: 99%
“…Studies have shown that the microbiota of encephalitis patients differed from that of healthy controls with alterations in SCFA production evident [ 68 ]. A decrease in butyrate- and propionate-producing species, including Faecalibacerium prausnitzii and A. muciniphila , is common in autoimmune diseases [ 35 ]. Systemic autoimmune diseases, e.g., RA, SLE and dermatological diseases (psoriasis) are characterized by an unusual adaptive immune response to autoantigens, specifically autoreactive T cells, which are a main driver of disease pathogenesis [ 70 ].…”
Section: Chronic Pain Conditionsmentioning
confidence: 99%